PENDAMPINGAN INOVASI GULA SEMUT PADA PENGRAJIN GULA AREN DI KABUPATEN OKU SELATAN - Sari, Fifian Permata; Munajat, Munajat (Jurnal Pengabdian Kepada Masyarakat (ABDIMAS) Universitas Baturaja, 2024)
Ant sugar or ant sugar is another preparation from palm juice or sugar palm (Arenga pinnata Merr), in crystal form like granulated sugar. The solid form of processed sap water is brown sugar or palm sugar. Ant sugar is rich in nutrition, containing calcium, minerals and vitamins which are very good for health. Its easy and practical form for mixing drinks and cakes makes this sugar much sought after abroad. That is why Indonesia is still an exporting country for ant sugar to this day. Simpang Sender Village is a central area for ant sugar craftsmen in OKUS Regency. During the Covid era, many businesses were affected, resulting in reduced sales turnover, including the ant sugar business. Problems in the form of uncertain production capacity, very traditional packaging and limited marketing have left many ant sugar craftsmen in increasingly worrying conditions. Promotion is still limited by word of mouth, limited product variations and low motivation from craftsmen, making this business increasingly worse even though opportunities for developing this business are still wide open. This business should be able to develop better with assistance and guidance to ant sugar craftsmen. The solution that can be given to ant sugar craftsmen is through assistance in the form of production management training (increasing production capacity and diversifying ant sugar products by modifying spice mixtures such as ginger and lemongrass extracts), business management training, digital-based marketing and improving packaging to attract attention. market. The technology for processing ant sugar with modified ginger and lemongrass will give rise to a new variant of ant sugar which can become a mainstay product typical of Simpang Sender Village, especially South OKU Regency. With taste innovation, attractive packaging and online marketing, it is hoped that it will be able to increase the income of palm sugar craftsmen in South OKU Regency